The Effect of Duolingo Media Application in Improving Arabic Vocabulary Mastery of Class VIII Students at MTsN 6 Nganjuk - Yazid, Ahmad; Ma’arif, M. Syamsul; Firdaus, M. Anang (Al-Wasil, 2023)
According to the students in grade VIII-1 of MTsN 6 Nganjuk Arabic language is one of the most frightening subjects. Because this lesson is quite difficult to learn without a teacher or companion, and in learning Arabic, it must not be learned in a hurry. In addition, the researcher also saw that students felt bored with the mufrodat memorization system through reading one by one from the book. With the Duolingo application, the researcher wanted to see if there was an increase in students' mastery of mufrodat and to see if language lessons became more fun and easy to learn.This study uses a quantitative approach. This type of research is a pre-experimental design or pre-experimental design, and uses a one group pre-test post-test design model. The sampling technique of this research used purposive sampling technique. The population of the study was a total of 276 class VIII, with a sample of 26 students from class VIII-1. The instrument used in this study is a test, namely for pre-test and post-test. In the study, the results showed that the Duolingo application had a positive influence on student learning outcomes, namely there was an increase in Arabic vocabulary mastery in class VIII-1 MTsN 6 Nganjuk. It can be seen that the pre-test has an average value of 74.7, and the post-test has an average value of 97.5. Meanwhile, according to the calculation of the t-test produces a value of tcount t= 6.977 where if it is included in the basis for decision making, then t count > t table or 9.718 > 2,060,. In addition, there is also a value of Sig. (2-tailed) which is 0.000. Which means 0.00 < 0.05 then H0 is rejected and H1 is accepted.